Changes in Urban Gas-Phase Persistent Organic Pollutants During the COVID-19 Lockdown in Barcelona - Prats, Raimon M.; van Drooge, Barend L.; Fernández, Pilar; Marco, Esther; Grimalt, Joan O. (Frontiers in Environmental Science, 2021)
The composition of polycyclic aromatic hydrocarbons (PAHs), polychlorobiphenyls (PCBs), hexachlorobenzene (HCB), pentachlorobenzene (PeCB), and organophosphate flame retardants (OPFRs) present in the gas-phase fraction of the atmosphere of Barcelona was analyzed during the SARS-CoV-2 coronavirus disease (COVID-19) lockdown and prior to this period. The changes in daily concentrations of CO, NO, NO2, O3 and particulate matter smaller than 10 μm (PM10) were considered for comparison. Bayesian analysis considering serial dependencies and seasonality showed statistically significant decreases of CO, NO, NO2, and PM10 (between −28 and −76%) and O3 increases (+45%) during lockdown. However, the lockdown concentration decreases of PeCB (−90.5%, from 8.5 to 0.8 pg m–3), HCB (−79%, 25.5–5.4 pg m–3) and some PAHs, such as benz[a]anthracene (−87%, 120–17 pg m–3) and pyrene (−81%, 3,500–680 pg m–3), were even stronger. The PAH depletion ranged between −68 and −87% that could be primarily associated with the strong reduction of traffic mobility during this period (−80%). Besides traffic reduction, the observed air quality improvements could be related to lower generation of solid urban residues (−25%) and the subsequent decrease of urban waste incineration (between −25 and −28%). Tributyl phosphate also showed a reduction in concentration during lockdown but the other OPFRs were seemingly not affected by this restriction, possibly as a result of the uniform release from the emission sources, e.g., construction material, industrial applications, and household products.